Expression, purification and folding of native like mitochondrial carrier proteins in lipid membranes - Tabefam, Marzieh; Smith, Matthew D.; Jelokhani-Niaraki, Masoud (Frontiers in Biophysics, 2024)
Mitochondrial Carrier Family proteins (MCFs) are located in the mitochondrial inner membrane (MIM) and play essential roles in various cellular processes. Due to the relatively low abundance of many members of the family, in vitro structure and function determination of most MCFs require over-expression and purification of recombinant versions of these proteins. In this study, we report on a new method for overexpression of MCFs in Escherichia coli (E. coli) membranes, efficient purification of native-like proteins, and their reconstitution in mitochondrial inner membrane lipid mimics. cDNAs of Uncoupling Protein 4 (UCP4), Adenine Nucleotide Translocase (ANT) and Phosphate Translocase (PiT) were subcloned into the pET26b(+) expression vector such that fusion proteins with a short N-terminal pelB leader sequence and a sixhistidine tag were produced to target the proteins toward the inner membrane of E. coli and facilitate affinity purification, respectively. Utilizing a modified autoinduction method, these proteins were overexpressed and extracted from the membrane of E. coli BL21 (DE3) and two modified strains, E. coli BL21 C43 (DE3) and E. coli BL21 Lobstr (DE3), in high yields. The proteins were then purified by immobilized metal affinity chromatography (IMAC) as monomers.Purity, identity, and concentration of the eluted monomers were determined by semi-native SDS-PAGE, western blotting and mass spectrometry, and a modified Lowry assay, respectively.Cleavage of the pelB leader sequence from proteins was verified by mass spectrometric analysis.The purified proteins, surrounded by a shell of bacterial membrane lipids, were then reconstituted from the mild non-denaturing octyl glucoside (OG) detergent into phospholipid liposomes.Monomeric UCP4 spontaneously self-associated to form stable tetramers in lipid membranes, which is consistent with our previous studies. However, PiT and ANT remained dominantly monomeric in both detergent and liposome milieus, as detected by a combination of spectroscopic and electrophoretic methods. Native-like helical conformations of proteins were then confirmed by circular dichroism (CD) spectroscopy. Overall, this study demonstrates that targeting MCF proteins to E. coli membranes provides an effective expression system for producing this family of proteins for biophysical studies.